Awareness, knowledge and attitude towards artificial intelligence in learning among faculty of medicine and health sciences students in University Tunku Abdul Rahman - Hwang, Ji Yen (2022)
With the advancement of computing and information processing tools, AI opens up new possibilities and chances in educational processes and can offer crucial insights to administrators and decision-makers at the institutional level in learning and education industry. Besides that, AI has been extensively used in educational systems, including intelligent tutoring systems, teaching robots, learning analytics dashboards, adaptive learning systems, and human-computer interactions, computing, and information processing techniques with the current advancement and industry revolution 4.0 (Kaur, 2021). Besides that, AI also found to be useful in medical field which acts as clinical educators and offers advice for health executives on how to encourage the use of AI in the education and professional growth of healthcare workers (Randhawa & Jackson, 2019) Therefore, the aim of this study was to determine the awareness, knowledge and attitude towards artificial intelligence in learning among MK FMHS students in UTAR. An observational descriptive study will be carried out to determine the awareness, knowledge and attitude towards artificial intelligence in learning among MK FMHS students in UTAR. Participants from Universiti Tunku Abdul Rahman, Sungai Long campus were recruited from FMHS. Awareness questionnaire were given to all the participants and required them to answer all the questions to determine the awareness, knowledge and attitude towards artificial intelligence in learning among FMHS students in UTAR. The awareness, knowledge and attitude of FMHS students were determined by scoring and were categorize them into three categories which are poor, fair and good. The data is recorded and categorised by IBM SPSS software statistics version 26. The total 272 responses collected, there were 8 participants who did not give consent to process the data. These data were removed from the data analysis process and hence there were only 264 responses were processed in the final stage of the study. The participants consist of 72% female and 28% male. There are 18.9% of TCM, 22.7% of MBBS, 5.7% of nursing and 52.7% of physiotherapy students participate in this study. The research found that 7.6% and 92.4% of participants have fair and good awareness respectively. While for knowledge part, 19.3% of participants have fair knowledge and 80.7% of participants have good knowledge towards AI in learning. However, more than 70% of them do not been taught about any AI related course. Generally, almost all the participants have positive attitude towards AI in learning. 16.3% of them have fair attitude while 83.3 of them have good attitude. However, there are 0.4% of participant has negative attitude towards AI in learning and more than 50% of participants have a fear that AI will replace the healthcare professions. In conclusion, it is found that FMHS students in UTAR generally have a good awareness and knowledge towards the basic of AI. However, they are not really understanding AI in-depth due to lack of opportunity to study in AI related course. Although there is a fear of replacement by AI, but majority of the students have a positive attitude towards AI in learning and agree that AI will be beneficial as learning tool. In addition, their willingness towards inclusion of AI in practical training and curriculum are also high. Hence, the university should consider including AI course in the syllabus to encourage the students to know and explore more about AI. Besides that, the university should also consider involving AI in practical learning and curriculum. This is giving the students a chance to learn through AI and adapt with the application of AI.